The Urgency of Multicultural Education in the Teaching and Learning Process of Public Universities in Indonesia and Malaysia - Suyurno, S. Salahudin; Fauzan, Umar; Fauzan, Muhammad Hendrie (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The integration of multicultural education in the teaching and learning process is essential for promoting equity, fostering intercultural understanding, and preparing students to navigate the complexities of our diverse and interconnected world. This is a comparative study in the context of Indonesia and Malaysia. The participant selection of this study used purposive sampling to select participants who have experienced the phenomenon of multicultural teaching. There are 10 participants from Indonesian public university and Malaysia public university involved in this study. To collect the data, the researchers conducted semi-structured interviews, observation, and documents. The researchers analyzed the data using the interactive model by Miles et al. that involves several interconnected steps, i.e., data condensation, data display, and data conclusion drawing/verification. The research found that the discourse of multicultural education in the teaching and learning process is very urgent for provoking equity, diversity, and social justice, as well as enhancing students' academic achievement. In the teaching and learning process of the Indonesian public university and Malaysia public university, multicultural education was implemented by incorporating culturally relevant content, implementing inclusive pedagogical practices, and fostering collaboration with communities. By embracing cultural diversity and promoting inclusive teaching practices, teachers can create transformative learning experiences that empower students to become informed, empathetic, and socially responsible global citizens.